Interferensi Bahasa Jawa dalam Bahasa Arab: Kasus pada Jamaah Yasin dan Tahlil Desa Crabak - Anggian, Lutvi Ali Sahana; Nurcahyaningtias, Novia Dwi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The interference of Javanese in Arabic in the yasin and tahlil congregation can be heard clearly in the pronunciation. Many members of the congregation adopted Arabic vocabulary, changing pronunciation and sentence structure to suit Javanese customs. For example, in prayer or dhikr, the pronunciation can sound more